2017
DOI: 10.1016/j.arr.2016.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition in early life and age-associated diseases

Abstract: The prevalence of age-associated disease is increasing at a striking rate globally. It is known that a strong association exists between a suboptimal maternal and/or early-life environment and increased propensity of developing age-associated disease, including cardiovascular disease (CVD), type-2 diabetes (T2D) and obesity. The dissection of underlying molecular mechanisms to explain this phenomenon, which is known as 'developmental programming' is still emerging; however three common mechanisms have emerged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 123 publications
1
54
0
Order By: Relevance
“…Strikingly, by age 3 years, MM of both sexes had surpassed controls in nearly every measure of body size. Human and animal studies have shown that rapid post‐natal catch‐up growth following poor intrauterine growth increases risk of age‐associated diseases . In humans, studies have documented that catch‐up growth is associated with early indicators of type 2 diabetes and obesity, endothelial dysfunction, hypertension, cardiovascular disease, and non‐alcoholic fatty liver disease .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strikingly, by age 3 years, MM of both sexes had surpassed controls in nearly every measure of body size. Human and animal studies have shown that rapid post‐natal catch‐up growth following poor intrauterine growth increases risk of age‐associated diseases . In humans, studies have documented that catch‐up growth is associated with early indicators of type 2 diabetes and obesity, endothelial dysfunction, hypertension, cardiovascular disease, and non‐alcoholic fatty liver disease .…”
Section: Discussionmentioning
confidence: 99%
“…Mismatch intrauterine growth increases risk of age-associated diseases. 24 In humans, studies have documented that catch-up growth is associated with early indicators of type 2 diabetes and obesity, 25,26 endothelial dysfunction, 27 hypertension, 28 cardiovascular disease, 29 and non-alcoholic fatty liver disease. 30 Similarly, experimental studies with rodents that were protein or calorie restricted in utero and TA B L E 5 Offspring morphometrics at birth in males and females then received obesogenic diets post-natally have shown reduced longevity, 31,32 obesity, 33,34 fatty livers, 35 insulin resistance, 36 hyperleptinaemia, 34 and hepatic fibrosis and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…If these adaptive modifications persist, or are more readily inducible later in life, they have the potential to promote energy absorption beyond metabolic capability when energy supplies increase, thereby causing insulin resistance, obesity and T2D in adulthood [9]. Among the factors affecting the risk of metabolic dysfunctions, including T2D, in adulthood, the prenatal and early postnatal malnutrition (both under- and overnutrition) is currently believed to be most important [10,11]. It should be noted that in this review only one aspect of malnutrition i.e., undernutrition but not overnutrition will be discussed.…”
Section: Conceptual Framework For Developmental Nutritional Programentioning
confidence: 99%
“…This can occur through the ‘sparing’ of certain vital organs, especially the brain, at the expense of other organs, including the heart, pancreas, kidney and skeletal muscle, resulting in compromised structure and function of these organs. Furthermore, if the suboptimal maternal environment is combined with a mismatched postnatal milieu, this can further exacerbate the increased risk of the development of a wide range of age-associated diseases in the offspring later in life (2). Despite decline in immune function being known to play an important role in the development of many age-associated diseases, it has been poorly studied in the context of developmental programming.…”
Section: Introductionmentioning
confidence: 99%